(untitled) (The Pakistan Development Review, 2000)
Non-governmental organisations (NGOs) continue to be the global ‘flavour of the month’ in international development. They are regarded as “outside” actors perceived to work in the interests of the poor, and in the absence of the state, many NGOs have taken on vital role in the provision of basic services to the poor. The institutional and political environment is attuned to privatisation in whatever form it takes. NGOs are another expression of this trend, but in the case of NGOs no real disillusionment phase has yet set in. But still NGOs remain the favoured vehicle for grass-roots involvement and community development in many countries. The present paper seeks to delineate the role of NGOs in micro finance and study their aggregate impact on poverty reduction in rural Pakistan as a result of micro finance efforts. The paper is organised in four sections. Section I commences with the concepts, promises and limitations of NGOs as a vehicle of micro finance. Section II summarises the record of performance of NGOs in Pakistan. In particular, the role, achievements and set-backs of two noted NGOs in Pakistan, Agha Khan Rural Support Programme (AKRSP) and National Rural Support Programme (NRSP). Which are studied by examining aggregate impact of these NGOs on poverty reduction as result of their micro finance efforts. Section III examines the poverty profile and presents summary of the role of NGOs in the context of poverty lending and, finally Section IV concludes the analysis and proposes some policy recommendations.